Peran Humas Diskominfo Dalam Mempublikasikan Kegiatan Pemerintah Melalui Media Sosial Instagram - Hessel, M Zackry; Razzaq, Abdur; Hati, Putri Citra (Komunika : Jurnal Ilmiah Komunikasi, 2025)
The development of information technology and the increasing use of social media have changed the way the government conveys information to the public, one of which is through Instagram, which has now become a means of publication and transparency for government agencies. In this context, the Public Relations Office of the Communication and Information Agency (Diskominfo) of Palembang City plays an important role in ensuring that information about government programs, activities, and policies can be published quickly, accurately, and easily understood. This study aims to analyze the role of the Public Relations Office of Diskominfo in publishing government activities through Instagram using a descriptive qualitative method through semi-structured interviews and field observations. The results of the study show that the Public Relations Office functions as a communication facilitator, expert advisor, communication technician, and liaison between the government and the public through the preparation of verified photo, video, infographic, and informative caption content before publication. The Public Relations Office also actively responds to questions and criticism from the public as part of two-way communication. However, there are obstacles such as limited human resources, the high volume of activities that must be published, and the demand for quick responses. These findings emphasize the need to strengthen team capacity and optimize social media management so that the publication of government activities through Instagram is more effective and consistent.